Neural correlates of emotion acceptance and suppression in borderline personality disorder - Fernando, Silvia Carvalho; Beblo, Thomas; Lamers, Agnes; Schlosser, Nicole; Woermann, Friedrich G.; Driessen, Martin; Toepper, Max (Frontiers in Psychiatry, 2023)
Background Emotion dysregulation is a central feature of borderline personality disorder (BPD). Since impaired emotion regulation contributes to disturbed emotion functioning in BPD, it is crucial to study underlying neural activity. The current study aimed at investigating the neural correlates of two emotion regulation strategies, namely emotion acceptance and suppression, which are both important treatment targets in BPD. Methods Twenty-one women with BPD and 23 female healthy control participants performed an emotion regulation task during functional magnetic resonance imaging (fMRI). While watching fearful movie clips, participants were instructed to either accept or to suppress upcoming emotions compared to passive viewing. Results Results revealed acceptance-related insular underactivation and suppression-related caudate overactivation in subjects with BPD during the emotion regulation task. Conclusion This is a first study on the neural correlates of emotion acceptance and suppression in BPD. Altered insula functioning during emotion acceptance may reflect impairments in emotional awareness in BPD. Increased caudate activity is linked to habitual motor and cognitive processes and therefore may accord to the well-established routine in BPD patients to suppress emotional experiences.